Measurements of ultra-low DC fields by high-T-c superconducting cores: The effect of calcination temperature - (:unkn) unknown (ELSEVIER SCIENCE SA, 2012)
In this study, the effects of weak links between grains of the ceramic superconductors on the sensitivity of a DC magnetic field sensor were examined. The evolution of 2nd harmonic signal strength, which determines the magnetometer sensitivity, with critical current density J(c) was especially analyzed. The J(c) values were adjusted by synthesis of Y-123 superconductors at different calcination temperatures. It was observed that the strength of 2f signal increases as the calcination temperature and so, the J(c) values increases. This is contrary to the common expectations. Our experiments have shown that the 2f signal changes quite linearly with DC field in a wide dynamic range (10(-4) to 10(-9) T) on the sample calcined at 950 degrees C. The ways of measuring DC fields as low as 1 nT are described in the paper. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 2nd harmonic signal; High-T-c superconductor; DC-magnetometer; Ultra-low DC field measurements; Magnetic field sensor; NONLINEAR ELECTRODYNAMICS; HARMONIC-GENERATION; SENSING INDENTATION; YBA2CU3O7 CERAMICS; MAGNETOMETER; SENSORS; MGB2; LOAD; YBCO